2004
DOI: 10.1186/1471-5945-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum TNF-α in psoriasis after treatment with propylthiouracil, an antithyroid thioureylene

Abstract: Background: Tumor necrosis factor-α (TNF-α) and its receptors play important roles in the development and persistence of psoriatic plaques. The antithyroid thioureylenes, propylthiouracil and methimazole, are effective in the treatment of patients with psoriasis with a significant number of patients showing clearing or near clearing of their lesions after a several weeks of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
6
2
1
Order By: Relevance
“…In addition, Nakamura et al [26] recorded a higher mean TNF-a serum level in patients with pustular psoriasis and palmoplantar pustulosis than controls. Moreover, TNF-a and its receptors play important roles in the development and persistence of psoriatic plaques [27]. In contrast to our finding is that of Tigalonova et al [28], who reported that the serum level of TNF-a did not differ between the psoriasis and the control groups.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, Nakamura et al [26] recorded a higher mean TNF-a serum level in patients with pustular psoriasis and palmoplantar pustulosis than controls. Moreover, TNF-a and its receptors play important roles in the development and persistence of psoriatic plaques [27]. In contrast to our finding is that of Tigalonova et al [28], who reported that the serum level of TNF-a did not differ between the psoriasis and the control groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Although mucosal involvements are rare, they are related to pustular, plaque-type and erythrodermic skin involvements. Also, various lesions have been described including white, yellowish, grey or translucent plaques, annular forms or diffuse areas of erythema and geographic tongue [ 12 , 13 ]. Although there is controversy about the occurrence of psoriatic lesions on oral mucous membranes, the results of a recent review showed that the prevalence of fissured tongue was ranging from 9.8% to 47.5% and geographic tongue occurred between 5.6% and 18.1% of patients with psoriatic disease [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, Kızıltunc et al [9] reported that IL-6 and TNF-α serum levels were decreased in humans who suffered owing to hypothyroidism. Contrarily to these data, PTU did not cause any alteration in circulating levels of TNF-α in human [10] nor in rats [11] . …”
Section: Discussionmentioning
confidence: 69%